Matching Needs to Services: Prison Treatment Program Allocations - Long, Joshua S. (Criminal justice and behavior, 2019)
The criminogenic needs of prison inmates are assessed to help guide their treatment plans, but inmates are often not matched to corresponding services to address those needs. A sample of 69,129 inmates in a state prison system was examined to identify those who completed treatment programs matched to their assessed needs and those who did not complete such programs. The odds of returning to prison within 3 years after release were compared for both groups. Of the eight need-specific domains examined, significant differences in the odds of prison returns were found for individuals identified with a Community Functioning need and for those identified with a Personal/Emotional need. That is, persons with either of these needs who completed suitable programs were less likely to return to prison compared with those with the same needs who did not complete suitable programs. Implications for future research are discussed.